Development of Thailand Reference Material for determining trace elements in drinking water - Thiengmanee, Usana; Kaewkhomdee, Nattikarn; Taebunpakut, Sutthinun; Yafa, Charun (Bulletin of Applied Sciences, 2022)
Certified reference material of determining trace elements in drinking water has been developed. It is so called Thailand reference material (TRM) issued by the National Institute of Metrology (Thailand) has been initiatively produced under the project of the ASEAN Food Testing Laboratory Committee (AFTLC). The TRM production was prepared from spiking appropriate amount of standard solution containing Cadmium (Cd) Copper (Cu) Iron (Fe) Zinc (Zn) and Lead (Pb) into acidic aqueous solution. This regards using valid procedures for homogeneity and stability studies implemented according to the requirement stated in ISO 17034 - ISO Guide 35 to ensure the quality of CRM. Their property values of TRM were characterized by exact-matching double isotope dilution mass spectrometric (IDMS) technique and their associated uncertainties were then estimated from characterization, homogeneity and stability studies. Referred to Policy on Measurement Traceability for Life Sciences Testing and Forensic Conformity Assessment Bodies (P113-A2LA), results for measurement comparison activities of the International Committee for Weights and Measures (CIPM) participated, e.g., SIM.QM.S2 SIM.QM-S7 and CCOM-K89, could be considered to support for becoming a prospective reference material producer in this region.